Meningkatkan Minat Belajar Siswa Kelas Viii Dengan Menggunakan Media Pembelajaran Canva Mata Pelajaran Ips Materi Mobilitas Sosial Di SMPN 4 Nangaroro Satap - Beda, Elias; Jun, Febrianita (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to prove and describe (1) implementation of canva learning media ini interest of class VIII students through the Canva learning media for the Social Studies subject, Social Mobility Material at SMPN 4 Nangaroro Satap, (2) The learning interest of class VIII students for the Social Studies subject, social mobility material after the application of the Canva learning media at SMPN 4 Nangaroro Satap. This research is a classroom action research (CAR) which is implemented in 2 cycles. The data collection techniques used are (1) observation, (2) documentation. The research subjects were 25 students of class VIII at SMPN 4 Nangaroro Satap. The results of the data analysis can be concluded that (1) Canva learning media has been implemented well in social studies learning on social mobility learning materials. This can be seen from Canva learning in cycle I of 72,5% (quite good category) and in cycle II of 95% (including the very good category). (2) Students interest in learning after applying Canva based increased in cycle I students interest learning was 75% (fairly good category) and the level in cicly II was 95 % (good category). This it can be suggested (a) teachers should be able to use a variety of learning media in teaching, one of which is Canva learning media as an alternative to increase students interest in learning. (b) Canva learning media is not only used in social studies subjects but can also be used in other subjects. (c) Schools are expected to facilitate teachers in the use of Canva learning media.